The Autobiographical Triangle – and Then What? - Małgorzata Czermińska (European Journal of Life Writing)
The essay outlines the key concepts of the universal theory of the autobiography, which I define as a “triangular” form of utterance involving three different stances: witness, confession, challenge. Witness refers to personal testimony to experiences lived through, confession to the presentation of intimate inner experience and challenge to the provocation of the reader to engage in dialogue, enter into an argument or join in a game. The three stances are always present, though usually one of them overshadows the other two. I present the prospects for the development of a variety of inspirations derived from this theory: 1) awareness not only of the existence but also of the growing significance of the stance of challenge; 2) destabilization of autobiographical place as a reference context for witness; 3) singling out of female autobiographical material and research on this topic; 4) the crisis in research on life writing in the context of the posthuman paradigm. My conclusion is a new proposal in the context of ecocriticism and animal studies: cohumanism instead of posthumanism.